The mummy case - Peters, Elizabeth, 1927-2013 (Peters, Elizabeth, 1927-2013. Amelia Peabody series., 2011)
Disgusted when he is denied access to the pyramids of Dahshoor, Egyptologist Radcliffe Emerson, aided by his archaeologist wife Amelia Peabody, finds his curiosity piqued when an antiquities dealer is murdered and a mummy case disappears.